A critical review of recent investigations on two-phase pressure drop in flow boiling micro-channels - Saisorn, Sira; Wongwises, Somchai (My University, 2012)
Two-phase pressure drop during flow boiling has been studied for several decades. Obviously, the publications available on micro-channels are relatively small compared with those for ordinarily sized channels. Although the use of micro-channels yields several advantages, the pressure drop taking p lace in these extremely small channels is higher than that in the ordinarily sized channels because of the increased wall friction. The knowledge of the two-phase pressure drop characteristics in addition to heat transfer phenomena is essential to the design and evaluation of the micro-systems. In this paper, recent research on the flow boiling pressure drop in micro-scale channels is reviewed. The experimental results as well as the relevant prediction methods based on different researchers are presented.
Keywords: Flow boiling; Heat transfer; Micro-channel; Pressure drop